A SYSTEMATIC LITERATURE REVIEW OF EMPLOYEE ENGAGEMENT AND JOB SATISFACTION WITH SPECIAL REFERENCE TO AGE, GENDER AND WORK EXPERIENCE - Pate, Mr. Mukund; Tharkude, Dr. Dhanashree (The journal of contemporary issues in business and government, 2023)
Job Satisfaction & Employee Engagement has gained significant attention in the recent times. Because of growing importance of job satisfaction & employee engagement, a lot has been studied in terms of research. Few researchers also extended their studies with employee engagement, job satisfaction & their relationship with demographics like work experience, race, employment type, age, education, income, marital status, gender etc. In this study, researcher has made an attempt to explore the relationship of select demographics i.e. age, gender, work experience with employee engagement and / or Job Satisfaction. This study is based on a secondary data which is gathered from papers, articles, thesis, surveys & online documents. A total of 105 articles / papers / theses / online documents has been studied as a part of literature review. Findings of this study shows that there is maximum number of literature studied for Gender as demographic compared to other demographics like Age & Work Experience in relationship with employee engagement and / or job satisfaction. Findings of this research can be useful for researcher for the knowledge implementation in employee engagement & job satisfaction research area with exploring extension of research beyond studied demographics in this paper. There can be a better future scope for any researcher to study the subject with different demographic or any particular demographic in detailed. Study in future scope can be explored for other constructs than studied in this paper i.e., employee engagement and job satisfaction. Future studies can be focused on specific countries and / or industries. It can be concluded that maximum number of studied literatures is from countries like USA & India in comparison to other countries. It is also observed that maximum number of studied literatures is from recent years like 2020, 2016, 2015 compared other years of publication. It is also seen that the construct Job Satisfaction is studied in maximum number of literature than employee engagement. Maximum number of literature has searched from google scholar & wiley databases compared to other databases.